Relationship between Self-Management Behavior on the Severity of Artery Coronary Disease - Marlina, Marlina; Sari, Muliya; Fithria, Fithria; Amni, Rahmalia (Universitas Islam Bandung, 2023)
Coronary artery disease (CAD) is a non-communicable disease that is the main cause of death and loss of disability-adjusted life years (DALYs) globally. Patients can experience various complications that affect the severity of the disease. Various factors, especially self-management behavior, can influence the severity of CAD patients. This study aimed to determine the relationship between self-management behavior and the severity of CAD in Dr. Zainoel Abidin Regional General Hospital Banda Aceh. This study used a cross-sectional design from March 28 to May 19, 2023. The sample consisted of 221 CHD patients who had undergone coronary angiography, were selected using purposive sampling, and met the inclusion and exclusion criteria. Data was collected through guided interviews using the self-management scale (CSMS) and syntax score. Data were analyzed descriptively and inferentially. Data analysis showed a significant relationship between self-management behavior and the severity of CAD. Daily life management (p=0.000, OR=5.334), disease management (p=0.000, OR=2.633), and emotional management (p=0.000, OR=2.047) were associated with the severity of CAD. Logistic regression indicated that daily life management was the most dominant factor associated with the severity of CAD (OR=5.334). Good daily life, disease, and emotional management can help reduce the risk of complications and improve the prognosis of CAD patients. Self-management behavior, particularly daily life management, is significantly related to the severity of CAD in Dr. Zainoel Abidin Regional General Hospital patients.